Structural Parametric Study of a Piezoelectric Energy Harvester for a Specific Excitation Frequency of an Electric Motor, Considering Fatigue Life - YANG, Ping; MOHAMAD USAMAH, Nabil; SAAD, Abdullah Aziz; AHMAD MAZLAN, Ahmad Zhafran (Archives of Acoustics, 2025)
Over the past decade, extensive research has been conducted in the field of piezoelectric energy harvesting, which drives advancements in novel designs and techniques. In this study, the vibration of an electric motor is characterized, and a piezoelectric energy harvester (PEH) beam with a natural frequency of 50 Hz is designed and fabricated. Then, the electromechanical characteristics of the PEH are simulated and tested through both finite element simulation and experiment. The validated simulation model can accurately predict the vibration characteristics of the PEH, which can be utilized for design improvements. Based on this beam structure, three sets of PEHs with different sizes are designed. A study of the output voltage and fatigue life of these different PEH sizes is conducted, and the relationship between the electromechanical coupling effect and its varying values is discussed. Based on the results, design schemes 1∼6 demonstrate advantages in terms of output voltage efficiency and fatigue strength, making them suitable for various environments and application purposes. This study establishes an efficient method for analyzing the structural parametric performance of piezoelectric cantilever beams, which paves the way for future research on fatigue-based structural design guidelines for PEH in electric motors.